SISTEM PRESENSI PERKULIAHAN MENGGUNAKAN PENGENALAN WAJAH BERBASIS EIGENFACE (STUDI KASUS PADA JURUSAN TEKNOLOGI INFORMASI UNIVERSITAS TADULAKO) - Prihastomo, Enggar Dwi; Dodu, Erwin; Joefri, Yuri Yudhaswana (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2016)
Digital era demands all thing could be done in computerized system to solve problems in easier way. So do with verification and identification system that continues to evolve with technology development. One of the implementations of it is face recognition. Human faces were taken as verification and identification system because they have unique characteristic and identity between one and others. Face recognition implementation on computerized system could be done with eigenface algorithm. Eigenface is one of face recognition’s algorithm based on Principal Component Analysis. Based on the best threshold value prospecting, it’s obtained for 2400, that value obtained for 100% of face recognition success rate. The image that can’t be detected and recognized as someone’s face is an image that has image distance error greater than predetermined threshold value and due to significant difference in light intensity of training images and test image.Keywords: Eigenface, Image, Euclidean Distance, and Face Recognition